O professor de língua inglesa na educação infantil: narrativas de formação e re(significação) - Kich, Bruna Viedo (2022)
This research project was developed in the Post-Graduate Program in Public Policies and School Management – Professional master’s degree at the Federal University of Santa Maria, in the research line “Pedagogical Management and Educational Contexts”. This study aims to answer the following research problem “How the process of becoming and recognizing oneself as a teacher is constructed in the path of English teachers who act in preschool education?”. It aims to understand how English teachers who act at the preschool level guide their practices and how they consolidate them along their trajectories. As literature review, it will present the main legal policies of teaching English in Brazil, studies about the formation of English teachers who act at the preschool level, and prominent theoreticians in the narrative research field, such as Bertaux (2011), Delory Momberger (2009), Ferraroti (2010), Josso (2004) e Pineau and Le Grand (2011). The methodology is composed of qualitative research, developed by the (auto)biographical method. It utilized documental research, bibliographical research, and semi-structured interviews. The subjects that will compose this study were delimited by the following criteria: a) be an English teacher; b) teach in Santa Maria/RS; c) work at the preschool level. After the interviews, which will be analyzed by semantics appreciation, categories of analysis and topics of category elements will be constructed. Qualitative data were analyzed using the Nvivo software, and grouped into main codes and sub codes, considering the recurrences of the speech. The three main codes are: Personal Genesis (considering their experiences in Elementary, Middle, and High school, and college students and their teaching experiences,focusing on everything that concerns them about their experiences and their subjectivities); Crossings (thinking of teaching as its intricacies and situations that crossed them and were somehow perceived or felt as a barrier or difficulty) and Professional Elan (experiences and perceptions of what brings teacher comfort and contributes to giving meaning to everyday practice). In the results, it was noticed that not all the subjects that participated on this research are professionally prepared for the exercise of the function, and that the movement of feeling able to do it is relating experience and training.